The Relationship between Exposure to Pornographic Media and Premarital Sexual Behavior in Adolescents: Hubungan Paparan Media Pornografi dengan Perilaku Seksual Pranikah pada Remaja - Lagani, Elviani; Arsyad, Gusman; Hadriani, Hadriani; Longulo, Olkamien Jesdika; Pont, Anna Veronica; Hadina, Hadina (Napande: Jurnal Bidan, 2024)
Background: According to data from the Talise Health Center, there are 98 people with HIV/AIDS in 2022, in 2023 there are 68 people, and the results of data collection from the Central Sulawesi Provincial BKKBN in 2022 Palu City is one of the areas with child marriage cases with a total number of married women of 37,166. Objective: to determine the relationship between exposure to pornographic media and premarital sexual behavior in adolescents at SMA Negeri 5 Palu City. Methods: This study used an analytical survey with a cross-sectional design, The research was conducted on March 6, 2024, at SMA Negeri 5 Palu City with a population of all students and students of classes X and XI as many as 594 people and a sample of 83 using the random sampling proportional technique. The research instrument used Google Forms, Univariate, and Bivariate data analysis using the Chi Square test. Results: showed that out of 83 people, there were 16 people (19.3%) were exposed to pornographic media and had risky behaviors, 28 people (33.7%), who were not exposed to pornographic media but had risky behaviors, 28 people (33.7%) who were exposed but had non-risky behaviors and there were 11 people (13.3%) who were not exposed to pornographic media and had non-risky behaviors. Based on the Chi-Square statistical test results, a P-value of 0.003  was obtained. Conclusion: there is a relationship between exposure to pornographic media and premarital sexual behavior of adolescents at SMA Negeri 5 Palu City. It is recommended  that schools activate religious activities so that adolescents can fortify themselves from exposure to pornographic media and premarital sexual behavior